Efficiency control of dietary pesticide intake reduction by human biomonitoring - Göen, Thomas; Schmidt, Lukas; Lichtensteiger, Walter; Schlumpf, Margret (International Journal of Hygiene and Environmental Health, 2017)
In spite of food safety controls for pesticide residues, a conventional diet still leads to a noticeable exposure of the general population to several pesticides. In a pilot study the response of exposure reduction by organic diet intervention on the urinary levels of pesticide metabolites was investigated. In the study two adult individuals were kept on a conventional diet for 11days and morning urine voids were collected at the last four days of the period. Afterwards, the participants switched to exclusively organic food intake for 18days and likewise morning urine samples were collected at the last four days of this period. In the urine samples six pyrethroid metabolites, six dialkylphosphates, four phenolic parameter for organophosphate pesticides and carbamates, 6-chloronicotinic acid (ClNA) as parameter for neonicotinoid insecticides, seven phenoxy herbicides, glyphosate and its metabolite AMPA were quantified using gas chromatographic mass spectrometric methods. Generally, the comparative analyses revealed greater shares as well as higher levels of the parameters in the samples taken during the common diet period compared to the organic diet period. Considerable decrease of the levels was found for almost all pyrethroid metabolites, dialkyphosphates and phenoxy herbicids, as well as for the phenolic metabolites 4-nitrophenol and 3,5,6-trichloropyridinol. In contrast, higher values were found for the organic diet period for ClNA and the metabolite of coumaphos in one of the volunteers. The present study confirms the results of former studies which indicated that an organic diet intervention results in considerable lower exposure to organophosphate pesticides and pyrethroids. It also verifies the former experience that monitoring of urinary parameters for non-persistent pesticides permits a reliable efficiency control of short-time effects by dietary interventions. Additionally to former studies, the results of the present study highlight the need of an extension of the parameter spectrum to all prominent pesticide groups.
EVALuna2:9773